1986
DOI: 10.1111/j.1748-1716.1986.tb07793.x
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical and metabolic characteristics of human skeletal muscle in relation to age

Abstract: Muscle fibre composition, fibre areas and enzyme activities were determined in muscle biopsy samples (m. vastus lateralis) from both legs of 34 clinically healthy men and 31 clinically healthy women (aged 20-70 years). No significant difference was found in any of the three variables between the right and left leg. In the whole material the mean percentage of type I fibres was significantly higher in men, whereas that of type IIA fibres was significantly higher in women (men 58% I, 27% IIA, 13% IIB, women 51% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
99
3
2

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(114 citation statements)
references
References 29 publications
10
99
3
2
Order By: Relevance
“…In addition, rising-from-chair motion in the intervention group of the present study improved both aspects of endurance and quickness, which is represented by the 86.0% improvement in maximum counts of continuous repetition and the 10.9% improvement in maximum count in 10 seconds. These results support the idea that regular exercise leads to improvement of both quickness and muscle strength in the elderly as mentioned by Fukunaga 14,15) , although quick motion which requires instantaneous force may cause injury since type I fiber (slow twitch fiber) is more greatly atrophied than type II fiber (fast twitch fiber) in the elderly in general [17][18][19] .…”
Section: Discussionsupporting
confidence: 73%
“…In addition, rising-from-chair motion in the intervention group of the present study improved both aspects of endurance and quickness, which is represented by the 86.0% improvement in maximum counts of continuous repetition and the 10.9% improvement in maximum count in 10 seconds. These results support the idea that regular exercise leads to improvement of both quickness and muscle strength in the elderly as mentioned by Fukunaga 14,15) , although quick motion which requires instantaneous force may cause injury since type I fiber (slow twitch fiber) is more greatly atrophied than type II fiber (fast twitch fiber) in the elderly in general [17][18][19] .…”
Section: Discussionsupporting
confidence: 73%
“…Isolated type 2 fiber atrophy was observed in both sexes especially from the 6 th decade onwards. The preferential involvement of type 2 fibers in aging has been widely studied by numerous authors 2,4,11,15,16,18,20,21 . Type 2 fibers are involved in diverse circumstances as a secondary phenomenon like disuse atrophy, upper motor neuron lesions, myasthenia gravis and steroid therapy [22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…A number of parameters of fiber size have been used by various investigators in their morphometric studies of muscle, particularly the cross-sectional area [1][2][3][4] and the lesser diameter [5][6][7][8] , or a combination of both 9,10 . It was also observed that most of the investigations on cross-sections of human skeletal muscle were made on the vastus lateralis and the available quantitative data were based on it [11][12][13] .…”
mentioning
confidence: 99%
“…For instance, it has been demonstrated that aged tissues exhibit dysfunctional complex IV of the ETC. This alteration mainly affects the muscle because it requires more energy than most other tissues and is also one of the tissues most affected by aging (25). It has been recently demonstrated that the decline in oxidative capacity is the primary contributing factor to age-related muscle atrophy (88).…”
Section: Cr Prevents the Decline Of Oxidative Capacity With Agingmentioning
confidence: 99%